From traditional fruit to modern functional food: chemical constituents, bioactive compounds, and therapeutic applications of Sukkari date palm (Phoenix dactylifera): a review - Ali, Rehab F. M.; El-Anany, Ayman M. (Frontiers in Nutrition, 2025)
The Sukkari date palm (Phoenix dactylifera L.) is increasingly recognized for its potential in sustainable agriculture due to its nutritional benefits and low environmental impact. This cultivar thrives in arid conditions, requiring minimal water, which aligns with the growing demand for sustainable food sources. Sukkari dates are rich in essential nutrients, including dietary fiber, vitamins, and minerals, which support overall health. They possess bioactive compounds with antioxidant, anti-inflammatory, and antimicrobial properties, making them valuable in functional food development. The cultivation of Sukkari dates can enhance economic stability in arid regions, providing livelihoods and contributing to local economies. Innovative uses in biodegradable packaging and bioenergy align with circular economy principles, promoting eco-friendly practices. While Sukkari dates present numerous advantages for sustainable agriculture, challenges remain in optimizing postharvest technologies and scaling up byproduct utilization to fully realize their potential benefits. Future research should address these areas to enhance the sustainability of date palm cultivation.